HUBUNGAN ASUPAN ENERGI DAN ASUPAN LEMAK TERHADAP PROFIL LIPID PADA PENDERITA DISLIPIDEMIA - Sugini (JURNAL GIZI DAN KESEHATAN, 2019)
Background :High energy intake from saturated fat increases the risk of CHD especially in women. This abnormallipid profile is closely related to the development process atherosclerosis. Epidemiological, laboratory and clinical studies show an association of increased incidence of cardiovascular disease and other degenerative diseases with high cholesterol levels. Method :The research design is cross-sectional. The subjects of the study were 30 employees of Kendal Hospital aged 35-50 years, suffering from dyslipidemia and not suffering from other metabolic or degenerative diseases based on the examination of a specialist in internal medicine. Examination of total cholesterol, LDL cholesterol were measured by vitros system chemistry analyzer 300 in the clinical pathology laboratory of Kendal Hospital. Food recall is done by using the food recall form through interviews conducted by trained and experienced nutritionists. Data analysis using Shapiro Wilk test and Spearman correlation test. Results: The results of the data analysis were thatthere was a strong correlation between fat intake and total cholesterol levels (p = 0.01, r = 0.593), there was a correlation between energy intake withtotal cholesterol levels (p = 0.016, r = 0.434),there was an intake correlationfat with LDL levels (p = 0.011, r = 0.456) and there was no correlation between energy intake and LDL levels (p = 0.1119, r = 0.291), Conclusion: There is a correlation between energy intake and total cholesterol (p = 0.016, r = 0.434), there is a strong correlation between fat intake and total cholesterol (p = 0.01, r = 0.593) and LDL (p = 0.011, r = 0.456). Abstrak : Latar Belakang : Asupan tinggi energi dari lemak jenuh meningkatkan risiko CHD khususnya pada wanita. Kelainan profil lipid ini erat hubungannya dengan proses perkembangan atherosklerosis. Penelitian epidemiologi, laboratorium dan klinik menunjukkan hubungan peningkatan kejadian penyakit kardiovaskular dan penyakit degeneratif lainnya dengan kadar kolesterol yang tinggi. Metode : Rancangan Penelitian adalah crossecional. Subyek penelitian adalah 30 karyawati RSUD Kendal umur 35 – 50 tahun.Pemeriksaan kadar kolesterol total, kadar kolesterol LDL diukur dengan vitros system chemistry analyser 300 di laboratorium patologi klinik RSUD Kendal. Asupan gizi diukur dengan metode food recall 24 dihitung dengan program Nutrisurvey. Analisis data menggunakan uji Shapiro Wilk dan uji korelasi Spearman. Hasil dan Pembahasan : Hasil analisa data adalah ada hubungan asupan energi dengan kadar kolesterol total (p=0,016, r=0,434), ada hubungan kuat asupan lemak dengan kadar kolesterol total (p=0,01, r=0,593), ada hubungan asupan lemak dengan kadar LDL (p=0,011, r=0,456) dan tidak ada hubungan asupan energi dengan kadar LDL (p=0,1119, r=0,291), Asupan tinggi energi mengakibatkan penimbunan lemak terutama trigliserida. Hal ini akan meningkatkan VLDL dan IDL darah yang akan berujung dengan peningkatan kolesterol total. Semakin tinggi seseorang mengkonsumsi makanan berlemak, maka timbunan kadar lemak dan trigliserida di dalam tubuh akan meningkat. Hal ini akan meningkatkan VLDL dan IDL darah. Simpulan : Ada hubungan asupan energi dengan kadar kolesterol total (p=0,016, r=0,434), ada hubungan kuat asupan lemak dengan kadar kolesterol total (p=0,01, r=0,593) dan kadar LDL (p=0,011, r=0,456).